Implementasi Sistem Layar Sentuh Pada Televisi Untuk menampilkan Denah Universitas Dirgantara Marsekal Suryadarma - Pramudya Saputra; Nurwijayanti K N (Universitas Dirgantara Marsekal Suryadarma, 2026)
The advancement of information technology has increased the need for interactive and easily accessible information media, particularly in campus environments with complex building layouts. Universitas Dirgantara Marsekal Suryadarma (Unsurya) still relies on conventional information media, which have limited flexibility and are difficult to update. This study aims to design, implement, and evaluate a touchscreen system on an LED television using an infrared touchscreen overlay as an interactive campus map display. An experimental method with a quantitative approach was employed by testing fingertip touch-area characteristics, screen response time in horizontal, vertical, and diagonal directions, and multi-touch capability. The results show that the fingertip touch area can be modeled as an ellipse with an average area of 640.56 mm² and an ellipse response time of 0.54 s. The average screen response times were 0.0494 s/cm in the horizontal direction, 0.0684 s/cm in the vertical direction, and 0.0459 s/cm in the diagonal direction. In addition, the system was able to detect up to ten simultaneous touch points. These findings indicate that the developed system demonstrates good performance and is feasible for use as an interactive information medium to support digital navigation services within the Smart Campus concept in a fast, intuitive, and real-time manner.